Examining Heisei Japan - Kitaoka, Shin'ichi 1948-; Kokubun, Ryo?sei 1953-; Nakanishi, Hiroshi 1962-; Shiraishi, Takashi 1950-; Tanaka, Akihiko 1954- (2021)
"The passing of Emperor Sho?wa marked the end of an era--an era memorable in both war and peace. As is the custom, the new emperor's reign was given a new name, in this case "Heisei," but this did not mean a reset on the international stage. The persistent diplomatic issues remained, and, furthermore, new issues arose. Promoting global peace and stability, preventing natural disasters, relations with China, regional cooperation, Japan's role in the international order are just some of the many outstanding issues. How did Japan approach them and deal with them? What was accomplished and what still needs to be done? Given the issues' paramount importance for both Japan and the world at large, this anthology brings together influential essays published by five of Japan's leading scholars during the period."
v. 1. Diplomacy and security --
Includes bibliographical references.
Keywords: Japan -- History -- Heisei period, 1989-.; Japan -- Foreign relations -- 1989-.; Japan -- Politics and government -- 1989-.; Japon -- Histoire -- 1989- (E?re Heisei).; Japon -- Relations exte?rieures -- 1989-.; Japon -- Politique et gouvernement -- 1989-.